I wonder why the telephone rings : and other questions about communication - Mead, Richard (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why The Telephone Rings is jam-packed with fascinating facts about communication, from 'How does your body talk?' to 'Is virtual reality just for fun?'.
Includes index
Keywords: Communication